Impact of frailty and its change on urinary incontinence: A longitudinal analysis from two prospective study of ageing - Xiaohan Gan; Linghao Meng; Shangqi Cao; Hexiang Bai; Xiang Li (PLoS ONE, 2025)
Background This study aimed to longitudinally investigate the impact of baseline frailty status and its changes over time on the risk of incident urinary incontinence (UI) in older adults, using data from two large prospective cohorts. Methods This study included community-dwelling older participants from China Health and Retirement Longitudinal Study (CHARLS) and Health and Retirement Study (HRS). Frailty status was assessed using a Frailty Index (FI) categorized as robust, pre-frail, and frail. Changes in frailty status were evaluated at baseline and at a second survey two years later. The primary outcome was incident UI, determined by participant self-report. Cox proportional hazard regression models were used to calculate Hazard Ratios (HRs) and 95% Confidence Intervals (CIs), adjusting for multiple covariates. Results In the baseline frailty status analysis, a total of 12,398 participants from CHARLS and 13,817 from HRS were included. Compared to robust participants, frail participants had a significantly increased risk of incident UI (CHARLS: HR 4.51, 95% CI 3.77–5.38; HRS: HR 2.25, 95% CI 2.07–2.46), and pre-frail participants also had a significantly increased risk (CHARLS: HR 2.14, 95% CI 1.79–2.55; HRS: HR 1.50, 95% CI 1.38–1.62). In the analysis of changes in frailty status, participants who progressed from robust to pre-frail/frail had a significantly increased risk of incident UI compared to those who remained robust (CHARLS: HR 2.81, 95% CI 1.94–4.08; HRS: HR 1.44, 95% CI 1.24−1.68). Conversely, participants who recovered from frail to robust/pre-frail had a significantly decreased risk of incident UI compared to those who remained frail(CHARLS: HR 0.51, 95% CI 0.41–0.62; HRS: HR 0.79, 95% CI 0.69–0.90). Subgroup analyses revealed similar results. Conclusion Frailty and worsening frailty status are significantly associated with an increased risk of Urinary Incontinence in older adults, while recovery of frailty status is associated with a decreased risk.